SOLIDARITAS SOSIAL PETANI PADI PADA TRADISI IRUTAN DI DESA KEDUNGMENTAWAR KECAMATAN NGIMBANG KABUPATEN LAMONGAN - Listya Dewi Surya; Ekna Satriyati (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Indonesia is a country rich in culture. In everyday life, people still apply traditions, norms and regional methods that apply in social life. One of the traditions that are still used in everyday life is the Irutan Tradition. A tradition that prioritizes active communication between participants to find solutions to problems experienced by farmers. The aim of this research is to explain the forms of the Irutan Tradition which encapsulate the social solidarity of the rice farming community in farming life as a local resistance in the current global era. This research uses a qualitative research method which describes the research results descriptively and uses a case study approach and uses a purposive sampling technique, namely determining informants based on certain characteristics. The results of this research are that the Irutan Tradition is a solution to farmers' problems when working on their rice fields regarding capital and tools... apart from that, the Irutan Tradition can also be a reinforcement of social solidarity in the Kedungmentawar Village community which has an impact on the emotional attachment of rice farmers so that can achieve a life of harmony and prosperity.